Complementary angles are two angles whose measures add up to 90 degrees.
In your case, one angle measures 36°, and the other angle measures \((x - 3)°\).
So we can set up the equation:
\[ 36 + (x - 3) = 90 \]
Now, simplify and solve for \(x\):
\[ 36 + x - 3 = 90 \] \[ x + 33 = 90 \] \[ x = 90 - 33 \] \[ x = 57 \]
Now, we can find the measure of the unknown angle:
\[ x - 3 = 57 - 3 = 54° \]
Thus, the values are:
- \(x = 57\)
- unknown angle measure = 54°
So, the final answers are: \(x = 57\), unknown angle measure = 54°.